Utilization Of E-Commerce To Increase Sales At Galeri Kopi Indonesia,Takengon - Lia Safrina; Dewi, Hartanti Dewi; Uswatun Hasanah; Badriah; Zulfikar (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
The development of technology, communication and computers encourages the growth of the community's economy that develops businesses online. The development of communication devices that make everyone who has a smartphone connected to the internet media makes it easier for prospective buyers to find the desired goods through their communication devices. So this online business is a very promising opportunity to be developed. The implementation of community service aims to apply e-commerce to the sale of coffee products. In the application of e-commerce to coffee products, it is necessary to provide insight to business actors to maintain product quality because it is related to buyer trust, providing complete and fast information, openness to E-Commerce information for Optimizing Product Marketing in the Digital Era for coffee shops Coffee Gallery in Takengon.